Analysis of the Implementation of the Drill Method in Developing Reading Skills in Indonesian Language Learning for Grade 2 Students at MI Terpadu Arrahman Palemban - Azzahra Nurul Nadilah; Midya Botty; Ines Tasya Jadidah (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study aims to investigate students’ reading ability, the implementation of the drill method in developing reading skills, and the supporting and inhibiting factors in its application. The research was conducted at MI Terpadu Arrahman Palembang. This is a qualitative study employing a descriptive research design. The data used in this study consist of primary and secondary data. Primary data were obtained directly without intermediaries, while secondary data were collected through intermediaries or literature review. Data collection techniques included observation, interviews, and documentation. Data analysis techniques consisted of data reduction, data presentation, and drawing conclusions. The results of this study indicate that: (1) The reading ability of second-grade students at MI Terpadu Arrahman is generally in the “fairly good” category. Students are able to read simple sentences, pronounce words correctly, and recognize letters accurately. Most students read fluently and have met the Minimum Competency Criteria (KKM) for basic reading skills. (2) The implementation of the drill method significantly aids students in developing reading skills, as this method emphasizes repetitive practice conducted in a structured and targeted manner. With this method, students become more fluent in recognizing letters, words, and sentences, as well as in proper pronunciation and intonation. (3) Supporting factors in the application of the drill method include a conducive learning environment, availability of facilities, high student motivation, and teacher competence. Family support such as parental involvement in home learning and concern for children's education also plays a key role. Inhibiting factors include students’ lack of focus during learning, shyness when asked to read aloud in front of the class, and boredom caused by repetitive activities, all of which pose challenges for teachers. External factors such as limited family support, restricted access to learning resources at home, and students’ socio-economic conditions also influence the implementation of the drill method.